MiR-223 as a Regulator and Therapeutic Target in Liver Diseases - Gu, Jiarong; Xu, Hao; Chen, Yandong; Li, Na; Hou, Xin (Frontiers in Immunology, 2022)
MicroRNAs (miRNAs) are endogenous non-coding single-stranded small molecule RNAs consisting of 20–24 nucleotides that are highly conserved in species evolution. Expression of miRNAs is strictly tissue-specific, and it is chronological in fungi and plants, as well as in animals. MiR-223 has been shown to play a key role in innate immunity, and dysregulation of its expression contributes to the pathogenesis of multiple inflammatory diseases, and cancers. In this article the biosynthesis and functions of miR-223 in innate immunity are reviewed, and the role of miR-223 in liver physiopathology and therapeutic prospects are highlighted.